Equations of state for astrophysical simulations from generalized relativistic density functionals. (17th September 2018) - Typel, S
Abstract: Simulations of astrophysical events such as binary neutron star mergers or core-collapse supernovae require detailed information on the properties of compact-star matter at finite temperatures. In this work new general-purpose equations of state are constructed. They are based on generalized relativistic density functionals with density-dependent couplings and include a full set of nuclei. The tables are provided in the CompOSE format. Predictions of thermodynamic quantities and the chemical composition of matter are compared with existing models of similar type along curves of constant entropy per nucleon. The focus is on effects of the employed cluster dissociation mechanism and the density dependence of the symmetry energy. A problem with the extraction of data from equation of state tables is identified.